Sensitivity analysis of factors influencing the reliability of reinforced concrete columns strengthened with Fabric-Reinforced cementitious matrix - Dang Cong-Thuat; Le Khanh Toan; Pham My; Dinh Ngoc Hieu (Tạp chí Khoa học và Công nghệ)
This paper presents a sensitivity analysis of key factors influencing the reliability of reinforced concrete columns strengthened with Fabric-Reinforced Cementitious Matrix (FRCM) with carbon fabric. Key parameters examined include axial force, concrete compressive strength, longitudinal reinforcement diameter, and stirrup diameter. Results indicate that axial force exerts the most significant impact on column reliability, with a notable increase in failure probability as axial force rises. Enhancements in concrete compressive strength and longitudinal reinforcement diameter improve reliability by reducing failure probability. Stirrup diameter and spacing are also critical for structural safety and collapse prevention. Furthermore, the analysis reveals that while higher axial force enhances the column's lateral load-bearing capacity, it concurrently reduces the structural ductility.